Complexos de Ru (II) com ligantes de interesse biológico: síntese, caracterização e citotoxicidade - Fleitas, Melina Andrea Mondelli (2011)
Three new Ru(II) complexes where were synthesized and characterized. The formulas were [RuCl(dmpm)2NO], [Ru(dmpm)2(dppb)] and [Ru(pic)2(dppb)], where dmpm = 4,6-dimethyl-2-mercaptopyrimidine, dppb = 1,4- bis(diphenylphosphine)butane e pic = picolinate ion. The characterization data are in agreement with the proposed formulation and also crystals were obtained and solved by X-ray diffraction. The resolution of the crystal structures confirmed the proposed structures, and demonstrated that they present distorted octahedral configuration. For [RuCl(dmpm)2NO], 1H RMN showed two singlets, at 7,3 and 6,7 ppm assigned to the hydrogen of the aromatic ring, and two singlets at 2,5 and 2,3 ppm assigned to aliphatic hydrogen. This differences could be explained by evaluating how the intermolecular hydrogen bonds are affecting the aliphatic hydrogen atoms present in the molecule and in the nearest neiborhood this differences could be explained evaluating the hydrogen bonds between neighbouring molecules. The infrared spectrum showed very intense band in 1857 cm-1 assigned to NO+ group. The cyclic voltammogram of this compound showed processes assigned to the nytrosil group, and electrolysis was performed to promote the NO release from the compound, which was confirmed by the disappearance of the NO+ band in the infrared spectrum of the complex. The complexes [Ru(dmpm)2(dppb)] and [Ru(pic)2(dppb)] showed singlets in 31P{1H} RMN at 47,5 and 46,2 ppm, respectively, and the cyclic voltammetry showed one process attributed to Ru III/ Ru II. The citotoxicity was evaluated for these three complexes (cells HeLa, MDA-MB231, V79 and U251 cells), obtaining promising values for [Ru(pic)2(dppb)] and [RuCl(dmpm)2NO] when compared with cisplatin (reference drug). Although, for [Ru(dmpm)2(dppb)], the value of IC50 wasn t as good as was found for the previous ones.